2021
DOI: 10.4054/demres.2021.45.44
|View full text |Cite
|
Sign up to set email alerts
|

Migration and demographic disparities in macro-regions of the European Union, a view to 2060

Abstract: BACKGROUNDMigration has become one of the most salient policy areas in the European Union. In response, the European Commission established a research team with the task of investigating a range of possible demographic futures. OBJECTIVEThis paper explores the demographic effects of migration on eastern, southern, and western EU regions, using different scenarios to see the extent population size, workingage population, education composition, and total age dependency can be influenced. METHODSWe use a determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…They also showed, however, that even in El Salvador, the no-migration alternative would not prevent ageing, but would merely reduce it (by roughly 15-20%). Furthermore, our conclusion that reduced emigration has a stronger effect on population size than on ageing is in line with results from Potančoková et al (2021). They found that while zero intra-EU migration would reduce the population decreases in Eastern EU from 18% to 10% and in Southern EU from 8% to 6% by 2060, the effects on the total age dependency ratios would be relatively minor.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…They also showed, however, that even in El Salvador, the no-migration alternative would not prevent ageing, but would merely reduce it (by roughly 15-20%). Furthermore, our conclusion that reduced emigration has a stronger effect on population size than on ageing is in line with results from Potančoková et al (2021). They found that while zero intra-EU migration would reduce the population decreases in Eastern EU from 18% to 10% and in Southern EU from 8% to 6% by 2060, the effects on the total age dependency ratios would be relatively minor.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, Chamie (2022, page 1) called the ageing of human populations "an inescapable demographic future"; and Coleman (2008, page 468) argued that "population ageing cannot be 'solved' ". Potančoková et al (2021) concluded that declines in the potential labour force and population ageing are clearly unavoidable in all of the EU's macro-regions, and that neither increased fertility nor increased migration are viable strategies for halting population ageing. Thus, these authors advised policymakers to aim to improve economic activity and productivity to accommodate for and adjust to the projected ageing, rather than to attempt to affect the demographic trends directly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations